A new species of Ficus (Moraceae) from the Cloud Montane Forests from Northeastern Peru - Reynel, Carlos (2025)
A new species of Ficus L. (Moraceae) from the montane cloud forest (CMF) in the Department of Cajamarca, northern Peru, is described here: Ficus huabalensis Reynel & J.L. Marcelo-Peña. This species belongs to the subgenus Spherosuke Raf. (formerly known as Urostigma Gasp.) and is distinguished by several vegetative and reproductive traits. It is a hemiepiphyte that develops into a free-standing tree, notable for its exceptionally long terminal stipule. It also bears minute (10x) brown hairs on the branchlets, petioles, blades beneath, and in the dorsum side of the receptacle bracts–always interspersed with minute whitish hairs. The species is currently known only from the Huabal District, where it inhabits a mature montane cloud forest.